Análisis Financiero a la Cooperativa de Ahorro y Crédito “Jardín Azuayo Ltda.” Sucursal – Loja. Periodos 2020 – 2021 - Montaño Pullaguari, Michelle Alejandra (2023)
At present, financial analysis is a tool used to generate financial information for entities that systematize, process, generate and present it through the accounting area. This analysis allows to know the financial health of companies from relative approaches (vertical analysis), its variations (horizontal analysis) and relating different items or accounts (financial indicators). Therefore, the purpose of this research was to perform a financial analysis of the Cooperativa de Ahorro y Crédito Jardín Azuayo Ltda. Loja Branch, periods 2020 - 2021, with the purpose of evaluating the economic and financial structure and the variations generated in the entity. The methodology used has a qualitative approach using deductive, inductive, analytical and synthetic methods to interpret the findings, where the Cooperativa de Ahorro y Crédito Jardín Azuayo was the object of study, and the time frame was between 2020 and 2021. Among the main findings, it was evidenced that approximately 87% of the assets were financed by liabilities in both years, likewise, the assets grew by 17.10% for the year 2021 with respect to 2020, growth that responds mainly to the increase in debt, regarding the financial indicators, it was determined that, in both years, the profitability was very low and that it presented good financial vulnerability indexes. Finally, it is concluded that the presentation of the financial analysis report allows the consolidation of information so that managers and directors can make the right decisions, as well as monitor the financial indicators presented.